Redox Regulation in Diazotrophic Bacteria in Interaction with Plants - Mandon, Karine (Antioxidants (Basel), 2021)
Plants interact with a large number of microorganisms that greatly influence their growth and health. Among the beneficial microorganisms, rhizosphere bacteria known as Plant Growth Promoting Bacteria increase plant fitness by producing compounds such as phytohormones or by carrying out symbioses that enhance nutrient acquisition. Nitrogen-fixing bacteria, either as endophytes or as endosymbionts, specifically improve the growth and development of plants by supplying them with nitrogen, a key macro-element. Survival and proliferation of these bacteria require their adaptation to the rhizosphere and host plant, which are particular ecological environments. This adaptation highly depends on bacteria response to the Reactive Oxygen Species (ROS), associated to abiotic stresses or produced by host plants, which determine the outcome of the plant-bacteria interaction. This paper reviews the different antioxidant defense mechanisms identified in diazotrophic bacteria, focusing on their involvement in coping with the changing conditions encountered during interaction with plant partners.